Gene Polymorphism of Aspirin-Induced Urticaria in Children With Kawasaki Disease - Zhang, Hui; Shi, Lin; Li, Xiao Hui; Zhang, Ming Ming; Lin, Yao; Liu, Yang; Li, Aijie (Frontiers in Pediatrics, 2019)
Objective: To investigate the distribution of the single nucleotide polymorphism (SNP) of LTC4S A-444C in children with Kawasaki disease in northern China and determine whether LTC4S A-444C SNP is associated with aspirin-induced urticaria (AIU). Methods: The clinical data of children with Kawasaki disease hospitalized in our centre from April 2015 to November 2017 were collected, and fluorescence in situ hybridization was used to detect the LTC4S A-444C. According to the genotype, the subjects were divided into three groups: AA genotypes, AC genotypes and CC genotypes. The incidence of AIU in the three groups was calculated and the relationship between LTC4S A-444C SNP and AIU was analyzed. Results: 1) A total of 574 children with Kawasaki disease were enrolled in the study. The allele frequencies for A, C were 980(85.4%), 168(14.6%). 2) 25 cases of AIU in AA genotypes, with a positive rate of 6%, 11 cases of AIU in AC genotypes, with a positive rate of 7.5%, 2 cases of AIU in CC genotypes, with a positive rate of 18.2%. CC genotypes had higher incidence of AIU than that of AA and AC genotypes. However, there was no significant difference among the three groups (P > 0.05). Conclusion: The proportion of CC genotypes of LTC4S A-444C in children with Kawasaki disease in northern China is lower than that of AA genotypes and AC genotypes, and the incidence of AIU of CC genotypes is higher than that of AC genotypes and AA genotypes.